A contextual study of co-worker relationship and turnover intentions: the mediating role of employee cynicism. Issue 2 (26th January 2022) - Abugre, James Baba; Acquaah, Moses
Abstract : Purpose: The purpose of the study is to evidently examine how employee cynicism mediates the relationship between co-worker relationship and employee turnover intentions in organizations in Ghana. Design/methodology/approach: Using a cross-sectional survey of employees from both public and private organizations, the authors tested our hypotheses with a sample of 288 employees by means of structural equation modelling (SEM) using maximum likelihood estimation with LISREL 9.2 and bootstrapping procedures. Findings: Findings showed that co-worker relationship is negatively associated with employee cynicism. The findings further revealed that employee cynicism is positively associated with employees' intention to leave. Additionally, employee cynicism negatively mediated the relationship between co-worker relationship and employee intention to leave their organizations. Practical implications: The work recommends that organizations become aware of employee cynicism which can adversely affects co-worker relationship and consequently organizational performance. Therefore, organizations ought to reduce employee cynicism and rather encourage positive co-worker relations through interpersonal relationship and support for employees. Originality/value: An investigation of co-worker relationship in organization and employee intentions to leave or turnover is a significant micro-level analysis for contemporary Human Resource Management (HRM) research. This study gives us a scarce opportunity to understand how employee cynicism negatively mediates the relationship between co-worker relationship and turnover intentions of employees.